Proteomics as tools for biomarkers discovery of adulteration in slaughtering procedures - Amid, Azura; Abu Samah, Norshahida (Zibeline International Publishing, 2019)
Slaughtering is an unavoidably sensitive issue among Muslim and Jews. This paper gives an outlook on possible detection methods in resolving the dilemma of religious slaughtering status. It will be rather easier to differentiate meat of different animal origins due to the exclusive genetic blueprint. However, in the case of adulteration in slaughtering procedure, the meat was taken from a similar source, thus, complicating the detection process. Therefore, an alternative approach employing proteomics were developed to identify protein expression patterns after external stimulation with electrical treatment. In the slaughtering process, the pain which is triggered by an external stimulus is expected to influence the protein profiles. Therefore, variations in stunning treatments which result in different patterns of protein profiles will pinpoint the specific biomarker for over stunned animals. This will inevitably help to detect adulterations in slaughtering procedure.